Seed priming agent for yield improvement and alleviation of moisture stress in rice (Oryza sativa L.) - Isiaka, Kareem (2016)
Yield improvement and alleviation of moisture stress are very important to achieve self-sufficiency in rice production. Therefore, this research was conducted to determine the efficacy of seed priming in yield improvement and moisture stress alleviation in MR219 rice. The first experiment was for determination of potential priming concentrations for MR219 production. It was found that calcium chloride, polyethyl glycol and kinetin priming were 73.91, 69.57 and 95.65% respectively better than the control. This was followed by the second experiment which focused on selecting the best priming durations for the selected priming agents for MR219 production under normal and moisture stressed conditions. From this experiment, for overall performance under both normal and stress conditions, calcium chloride, polyethyl glycol and kinetin priming were 33.74, 26.86 and 23.69% respectively better than their respective alternate priming duration in yield production. The efficacy of the selected priming agents was tested against pre-germination under normal and moisture stress conditions. It was found that 100 ppm kinetin priming was 12% better than pre-germination under normal condition in grain yield. When stress was imposed at tillering and post-anthesis stages, the grain yield from 100 ppm kinetin priming was 12.39 and 30.10% respectively better than pre-germination. However, none of the priming treatments could improve the yield of MR219 rice when moisture stress was imposed at pre-anthesis stage. Based on this result, a 24-hour priming with 100ppm kinetin was selected for detailed physiological and biochemical studies under moisture stress. It was found that the betterment of 100 ppm kinetin over pre-germination was found that the betterment of 100 ppm kinetin over pre-germination was 91.84% in primary chlorophyll fluorescence, 36.84% in maximum quantum yield of photosystem II, 6.84% in intercellular carbon dioxide, 16.67% in transpiration rate, 6.54% in cell membrane thermo-stability, 17.88% in relative injury, 43.03% in water use efficiency, 31.88% relative water content, 36.35% in superoxide dismutase, 28.78% in anthocyanin, 22.17% in proline, 14.67% in total phenol, 5.88% polyphenol, 16.04% in peroxidase activity, 17.28% in phenylalanine ammonia lyase activity, 27.88% in ascorbate oxidase activity, 5.16% in ascorbate peroxidase activity, 11.40% in hydrogen peroxide, 21.38% in lipid peroxidation, 34.61% in number of tillers,10.24% in plant height, 33.33% in productive tillers and 12.39% in yield as compared with the control. All these results explain the vegetative stability of the plants when they were stressed.